Erythropoietin in gynecological oncology - Dańska, Anna; Sodowski, Krzysztof; Przybylski, Marcin; Spaczyński, Marek (Contemporary Oncology/Współczesna Onkologia, 2002)
Malignant neoplasms of female genital organs remain more and more important problem and difficulty for both gynecologists and oncologists. The increasing number of cancer patients makes search for better methods of early detection and more effective treatment. Anaemia is frequently seen in non-haematological malignancies, and is associated with poor tumor oxygenation, debilitating fatigue, subsequent reduced quality of life, and limitation of further therapy. An important issue, which has not been sufficiently evaluated, is that anaemia also may adversely influence the outcome of cancer treatment. Although oncologists realize that patients suffer from fatigue, the understanding of etiology and possible interventions seldom seems to be put into the practice and has not been implemented in the routine management of cancer anaemia. The pathogenesis of anaemia is multifactorial, including tumor disease and cancer treatment, and resembles anaemia in other chronic diseases. Aneamia is traditionally treated by transfusions with an immediate, but transient effect on haemoglobin levels. The introduction of erythropoietin (EPO) now offers a new approach to manage anaemia by acting on patients own blood cells and thus avoiding the risks and problems associated with transfusions. EPO is well tolerated, and approximately 60% of patients treated respond with increased haemoglobin levels, reduced fatigue and obviously increased quality of life. This paper summarises the present evidence-based knowledge regarding cancer-related anaemia and the use of erythropoietin in gynecological malignancies. Also own experience related to the use of EPO in the treatment of ovarian cancer is presented. Chemotherapy based on platinum courses is always used adjuvant yteratment for ovarian cancer. There were losts of studies dealing with the efficacy of EPO treatment of chemotherapy-induced anaemia in patients with ovarian cancer after platinum-based therapy. The results show that EPO increases haemoglobin concentration and haematocrit level, and diminishes the need for transfusions in platinum-based schedules. That not only improves the quality of life, but allows futher treatment that should be stopped in anaemic patients.